Can Information Campaigns Spark Local Participation and Improve Outcomes? A Study of Primary Education in Uttar Pradesh, India - Banerjee, Abhijit; Banerji, Rukmini; Duflo, Esther; Glennerster, Rachel; Khemani, Stuti (World Bank, Washington, DC, 2012)
There is a growing belief in development policy circles that participation by local communities in basic service delivery can promote development outcomes. A central plank of public policy for improving primary education services in India is the participation of village education committees (VECs), consisting of village government leaders, parents, and teachers. The authors report findings from a survey in the state of Uttar Pradesh, of public schools, households, and VEC members, on the status of education services and the extent of community participation in the public delivery of education services. They find that parents do not know that a VEC exists, sometimes even when they are supposed to be members of it; VEC members are unaware of even key roles they are empowered to play in education services; and public participation in improving education is negligible, and correspondingly, people's ranking of education on a list of village priorities is low. Large numbers of children in the villages have not acquired basic competency in reading, writing, and arithmetic. Yet parents, teachers, and VEC members seem not to be fully aware of the scale of the problem, and seem not to have given much thought to the role of public agencies in improving outcomes. Learning failures coexist with public apathy to improving it through public action. Can local participation be sparked through grassroots campaigns that inform communities about the VEC and its role in local service delivery? Can such local participation actually affect learning outcomes, and can any impact be sustained? The authors describe information and advocacy campaigns that have been experimentally implemented to address some of the problems with local participation, and future research plans to evaluate their impact.